PERENCANAAN KEUANGAN SYARIAH BAGI KELUARGA PADA DESA CIBENING, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Suryani, Ermi; Melinasari, Susi; Munir Mubarok, Muhamad Misbahul (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
In the context of community service, as well as socializing sharia financial planning for families to the people of Cibening Village, Pamijahan District, Bogor Regency, West Java Province, was well received by the community and the community was also able to understand the importance of planning family finances in accordance with Sharia recommended so that each family is able to control finances and plan for the future of the family. Sharia financial planning is a method for planning family finances in the present and the future which does not violate the rules of Islamic law, this Sharia financial planning includes household bookkeeping, making cash flow records, knowing healthy or ideal family finances, transactions that are prohibited religion, set financial goals.